Управління кредитним ризиком банку на основі методу диверсифікації - Гринько, Олена; Хохлов, Володимир; Корягіна, Ганна; Hrynko, Olena; Volodymyr, Khokhlov; Koryagina, Anna (ТНЕУ, 2008)
Розглянуто питання вдосконалення методики диверсифікації кредитного портфеля банку, запропоновано економіко-математичну модель диверсифікації кредитного ризику сукупного портфеля кредитів банку, що дозволяє врахувати можливу надмірну диверсифікованість і визначити оптимальну глибину диверсифікації. The questions of improvement of a cumulative bank credits portfolio diversification method, the economic-mathematical model of a cumulative bank credits portfolio diversification are offered in the article. The model allows to consider possible excessive diversification and to define optimal diversification intensity.
Bank credit risk management on the basis of diversiﬁcation method